2014
DOI: 10.5539/gjhs.v6n7p23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Verapamil Efficacy in Peyronie’S Disease Comparing With Pentoxifylline

Abstract: Introduction:Peyronie’s disease described as penile curvature, fibromathosis and pain that occur most often in men aged 40 to 60 years. The main complaint that caused the patient to visit the clinic is nodules on the upper surface of the penis, causing curvature and distortion particularly during erection, but they don’t have any urinary problem. In this study, we evaluated the effect of verapamil compared to pentoxifylline in Peyronie’s disease.Method:In this study, 90 patients with signs and symptoms of Peyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…As other authors previously reported, we decided to use PTX to treat PD in its initial, not yet stabilized phase, 31 , 32 intrigued by the interesting properties of PTX, which has been used since 1976 and is commonly employed to treat circulatory disorders, in particular in chronic peripheral artery disease. 55 , 56…”
Section: Discussionmentioning
confidence: 99%
“…As other authors previously reported, we decided to use PTX to treat PD in its initial, not yet stabilized phase, 31 , 32 intrigued by the interesting properties of PTX, which has been used since 1976 and is commonly employed to treat circulatory disorders, in particular in chronic peripheral artery disease. 55 , 56…”
Section: Discussionmentioning
confidence: 99%
“…Physical barriers to disabled patients, such as stairs, doorways, elevated examining tables, are the most obvious, and arguably the easiest to eliminate. Family physicians have been shown to be resourceful and adaptive in their attempts to improve access despite physical barriers Typical accommodations include seeing patients at an alternate accessible site, examining patients in their wheelchairs, rather than transferring to an examining table, making home visits, communicating by phone, email or skype [ 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility and human rights legislation in most jurisdictions is aimed at ensuring this most basic aspect of access; and yet, as Pharr [ 33 ] notes, even where practice administrators are aware of the legislation, there is no assurance that accessibility standards will be met. Osmun, Chan and Solomon [ 15 ] outline medical, legal and ethical considerations associated with providing primary care to people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the aforementioned therapies, large‐scale and well‐controlled trials have been lacking despite promising results for limited patient cohort sizes in both the acute/early and chronic/mature PD populations [30–32]. Intralesional verapamil has also been used in combination with oral antioxidant therapy with objective responses in penile curvature reduction, plaque size lessening, and erectile function improvement [33,34]. Other combinations with iontophoresis and topical therapy have been reported with favorable results [35,36].…”
Section: Introductionmentioning
confidence: 99%